Effect of Time of Planting and Auxins on Rooting of Cutting of Ker (Capparis decidua Forsk.) - Meghwal, P R; Vashishtha, B B (Annals of Arid Zone, 2016)
An experiment was conducted on the response of hardwood cutting of ker (Capparis decidua Forsk,) to time of planting and auxin treatments Juring 1994-95. Significant differences were recorded in per cent sprouting and rooting between July-August and September-February planted cuttings irrespective of auxin treatments. Significantly higher number of roots were produced in August planting compared to September and February. Significant differences were also found under different times of planting in respect of root length. Auxins failed to cause any significant increase in rooting over the control, although beta naphthoxy acetic ’acid had significant influence on number and length of roots and shoots.